ZmPUMP encodes a fully functional monocot plant uncoupling mitochondrial protein whose affinity to fatty acid is increased with the introduction of a His pair at the second matrix loop - Fávaro, Regiane Degan [UNESP]; Borecký, Jiri; Colombi, Débora [UNESP]; Maia, Ivan de Godoy [UNESP] (Elsevier, 2006)
Uncoupling proteins (UCPs) are specialized mitochondrial transporter proteins that uncouple respiration from ATP synthesis. In this study, cDNA encoding maize uncoupling protein (ZmPUMP) was expressed in Escherichia coli and recombinant ZmPUMP reconstituted in liposomes. ZmPUMP activity was associated with a linoleic acid (LA)-mediated H+ efflux with Km of 56.36 ± 0.27 μM and Vmax of 66.9 μmol H+ min-1 (mg prot)-1. LA-mediated H+ fluxes were sensitive to ATP inhibition with Ki of 2.61 ± 0.36 mM (at pH 7.2), a value similar to those for dicot UCPs. ZmPUMP was also used to investigate the importance of a histidine pair present in the second matrix loop of mammalian UCP1 and absent in plant UCPs. ZmPUMP with introduced His pair (Lys155His and Ala157His) displayed a 1.55-fold increase in LA-affinity while its activity remained unchanged. Our data indicate conserved properties of plant UCPs and suggest an enhancing but not essential role of the histidine pair in proton transport mechanism. © 2006 Elsevier Inc. All rights reserved.
Keywords: Functional reconstitution; Maize; Mitochondrial carriers; Plant mitochondria; Proton transport; UCP; Uncoupling mitochondrial protein; adenosine triphosphate; alanine; complementary DNA; fatty acid; histidine; linoleic acid; liposome; lysine; mitochondrial protein; controlled study; Escherichia coli; mammal; nonhuman; pH; plant; priority journal; protein expression; protein function; proton transport; Adenosine Triphosphate; Amino Acid Substitution; Carrier Proteins; DNA, Complementary; Fatty Acids; Histidine; Ion Channels; Kinetics; Linoleic Acid; Liposomes; Membrane Proteins; Mitochondrial Proteins; Mutation; Plant Proteins; Protons; Recombinant Proteins; Zea mays; Mammalia